Towards enabling better evaluation of emphysema: investigation into a method to reduce the variability of lung CT attenuation values due to patient size and positioning - Haase, Viktor; Noo, Frédéric; Stierstorfer, Karl; McNitt-Gray, Michael (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2022)
Chronic obstructive pulmonary disease (COPD) is a leading cause of patient mortality and morbidity. Measuring the amount of emphysema via a non-contrast CT scan plays a major role in the assessment of COPD and possible treatment options. We are interested in evaluating variability in lung CT attenuation values, which directly impacts emphysema scoring. Our investigations are focused on bias in these values due to patient size and positioning effects, as well as a method to reduce this bias. An anthropomorphic lung phantom was scanned in both centered and off-centered positions. Furthermore, patient size variation was simulated using a home-made fat belt. The obtained projection data was first pre-processed and reconstructed as conventionally done on the scanner, then pre-processed with a proposed correction pipeline that is designed to reduce scatter and beam hardening errors in a patient-specific manner. The images from the scanner show that off-centering the phantom changes the difference in mean value between the left and right lung, from 1.5 to 6.5 HU. Moreover, with the fat belt, the mean value in both lungs increases by more than 13 HU and the inhomogeneity of the lung tissue, measured with the standard deviation, nearly doubles with presence of a strong cupping artifact. Using the proposed method to reduce bias, the mean values of the left and right lung are generally closer to each other, the inhomogeneity is either reduced or unchanged, and the cupping artifact is much less pronounced. This is expected to allow more robust emphysema scoring.
CRIS-Team Scopus Importer:2022-06-10
Keywords: beam hardening; COPD; emphysema score; image quality; lung imaging; Quantitative CT; scatter